Normative Vorstellungen von Schulklassen - Hübner, Marco (Universitätsverlag Göttingen, 2022)
Although the school class is highly relevant for the school organization of instruction, it is predominantly addressed in empirical school research as an explanandum. The sociality of the school class, on the other hand, has hardly been focused on as an empirical object of research. The aim of this paper is to address this desideratum by considering the school class as an object that is constituted in a variety of ways in different discourses. It also asks how classroom teachers construct the school class in everyday-based discourse and relate themselves to it. Different types of data are used to examine how which normative conceptions of school classes are produced in educational, programmatic, and everyday-based discourse. Contributions in scholarly and contemporary practice-instructional literature, as well as specially collected interviews with classroom teachers in secondary schools, serve as data materials. The interviews, as well as the idea for this study, were developed within the framework of the project on making school classes at the Department of Empirical Research on Teaching and School Development at the Institute of Educational Science at the University of Göttingen. Translated with www.DeepL.com/Translator (free version)